Bis(tetraethylammonium) bis(dimethylformamide)tetrakis(μ-N,2-dioxidobenzene-1-carboximidato)pentacopper(II) - Herring, Jacob (International Union of Crystallography, 2011)
The title compound, (C(8)H(20)N)(2)[Cu(5)(C(7)H(4)NO(3))(4)(C(3)H(7)NO)(2)], abbreviated as (TEA)(2)[Cu(II)(12-MC(Cu(II)) (N(shi))-4](DMF)(2) [where TEA is tetraethylammonium, shi(3−) is salicylhydroximate (or N,2-dioxidobenzene-1-carboximidate) and DMF is N,N-dimethylformamide], contains five Cu(II) ions. Four of the Cu(II) ions are members of a metallacrown ring (MC), while the fifth Cu(II) is bound in a central cavity. Two of the ring Cu(II) ions are five-coordinate with distorted square-pyramidal geometry. The coordination sphere is composed of two shi(3−) ligands and one DMF molecule. The other two ring Cu(II) ions and the central Cu(II) ion are four-coordinate with square-planar geometry. The coordination spheres of these ions are only composed of shi(3−) ligands. The charge of the [Cu(II)(12-MC(Cu(II)) (N(shi))-4](2−) unit is balanced by two uncoordinated TEA(+) countercations. The structure shows severe static disorder with the metallacrown, the tetraethylammonium cations and the DMF solvent molecule all disordered over each of two mutually exclusive sites, with occupancy rates for the major moieties of 0.6215 (6) for the metallacrown, 0.759 (3) for the tetraethylammonium ion and 0.537 (6) for the DMF molecules. The metallacrown unit is located on a crystallographic inversion center and disordered about a non-crystallographic twofold axis. The DMF molecule and the tetraethylammonium ion are disordered about a non-crystallographic twofold axis and pseudo-inversion center, respectively.